Spatiotemporal variations in hydroclimate across the Mediterranean Andes (30°-37°S) since the early twentieth century - González Reyes, Álvaro (2017)
In the Mediterranean Andes region (MA; 30°-37°S), the main rivers are largely fed by melting snowpack and provide freshwater to around 10 million people on both sides of the Andes Mountains. Water resources in the MA are under pressure because of the extensive development of industrial agriculture and mining activities. This pressure is increasing as the region faces one of its worst recorded droughts. Previous studies have pointed to El Niño-Southern Oscillation (ENSO) as the main climatic force impacting the MA. However, the role of decadal and multidecadal climate variability, their spatial patterns, and the recurrence of long-term droughts remains poorly studied. In an attempt to better understand these factors, spatial and temporal patterns of hydroclimatic variability are analyzed using an extensive database of streamflow, precipitation, and snowpack covering the period between 1910 and 2011. These analyses are based on the combination of correlation, principal components, and kernel estimation techniques. Despite a general common pattern across the MA, the results presented here identify two hydroclimatic subregions, located north and south of 34°S. While the interannual variability associated with ENSO is slightly stronger north of 34°S, the variability associated with the Pacific decadal oscillation (PDO) and/or the interdecadal Pacific oscillation (IPO) index shows similar patterns in both regions. However, variations produced by the IPO forcing seem to be greater in the southern subregion since 1975. The estimations presented here on drought recurrence reveal a generalized increase in dry extremes since the 1950s. These findings suggest that the northern MA is more vulnerable to changes in hydrology and climate than the southern MA.